Sensitivity and specificity of the Distress Thermometer for depression in newly diagnosed breast cancer patients - Hegel, Mark T. (2008)
BACKGROUND: Receiving a new diagnosis of breast cancer is a distressing experience that may precipitate an episode of major depressive disorder. Efficient screening methods for detecting depression in the oncology setting are needed. This study evaluated the receiver operating characteristics (ROC) of the single-item Distress Thermometer (DT) for detecting depression in women newly diagnosed with Stage I–III breast cancer. METHODS: We assessed 321 patients (of 345 consecutive patients) at the time of their pre-surgical consultation at a Comprehensive Breast Cancer Program. Patients were administered the DT along with the Patient Health Questionnaire 9-Item Depression Module (PHQ-9) as a gold standard diagnostic assessment of depression status. RESULTS: Mean DT scores (11-point scale, 0–10) were significantly higher for depressed versus non-depressed patients (8.1 versus 4.4). In ROC analyses the DT showed strong discriminatory power relative to the PHQ-9-derived diagnosis of depression, with an area under the curve of 0.87. Patient age, education, marital status and stage of disease resulted in similar operating characteristics. A score of 7 represented the optimal trade-off between sensitivity (0.81) and specificity (0.85) characteristics for detecting depression. CONCLUSIONS: The single-item DT performs satisfactorily relative to the PHQ-9 for detecting depression in newly diagnosed breast cancer patients. A cutoff score of 7 on the DT possesses the optimal sensitivity and specificity characteristics. The strength of these findings suggests that a careful psychosocial evaluation should follow a positive screen.